The effect of adding dexamethasone to intracuff lidocaine 2% on decreasing the respiratory complications after general anesthesia: a randomized, double blind, clinical trail - Mansour Choubsaz, Nasrin Amirifard, Masoud Sadeghi , , Edris Sadeghi, Zahra Johari (Journal of Applied Pharmaceutical Science, 2016)
Postoperative sore throat and other airway morbidities are common and troublesome after endotracheal intubation general anesthesia. The aim of this study was to evaluate the effect of dexamethasone added to intracuff lidocaine on decreasing the respiratory complications after general anesthesia. In a retrospective study, 207 patients that were under general anesthesia and scheduled for tracheal intubation, randomly divided to four groups based on endotracheal tube cuff filling (48 patients with air (group A), 52 patients with lidocaine 2% (group L), 54 patients with dexamethasone 4mg (group D) and 53 patients with lidocaine 2% plus dexamethasone 4mg (group LD)). Chi-square test used to compare two categorical variables or T-test for to compare the means in two variables. P-value
Keywords: General anesthesia,Lidocaine,Dexamethasone,Sore throat.